Do disasters trigger protests? A conceptual view of the connection between disasters, injustice, and protests—The case of COVID-19 - Vestergren, Sara; Uysal, Mete Sefa; Tekin, Selin (Frontiers in Political Science, 2022)
People around the globe are affected by disasters far beyond the disaster properties. Given that certain social groups are affected disproportionately, disasters need to be considered as political events which may cause political actions. Therefore, we aim to discuss, from a social psychological perspective, how and why protests might occur during or after a disaster. We argue for an elaborated model of collective action participation suggesting that disasters enhance the predictors of protest mobilization and participation though emerged or enhanced social injustice. We also suggest that disaster properties can be used to delegitimise protests and social movements, limiting the mobilization and collective resilience during and after a disaster. Finally, we discuss the gaps in current research and emphasize the need for more attention to the disaster-protest link as we can expect more disasters due to climate crisis, likely to lead to more protests and political collective action.